Ultrasound-driven anaerobic digestion to improve energy production from crude glycerol - Martins, Ramiro J. E. (Edelweiss Applied Science and Technology, 2024)
Anaerobic digestion of crude glycerol derived from biodiesel production is being studied as an alternative to valorization through methane production. The high organic load (1800 g COD L-1) of crude glycerol can cause kinetic stress, leading to inhibition of methanogenic microorganisms. To overcome this issue, an alternative approach is the use of ultrasound energy, which promotes cell wall and membrane disruption and releases intracellular material that enhances biodigestion. Considering this alternative, the main objective of this study was to test ultrasound pretreatment to facilitate the subsequent anaerobic digestion of crude glycerol.